2021
DOI: 10.1007/s10055-021-00539-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spatial orientation skill between real and virtual environment

Abstract: Virtual reality (VR) is a promising tool and is increasingly used in many different fields, in which virtual walking can be generalized through detailed modeling of the physical environment such as in sports science, medicine and furthermore. However, the visualization of a virtual environment using a head-mounted display (HMD) differs compared to reality, and it is still not clear whether the visual perception works equally within VR. The purpose of the current study is to compare the spatial orientation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Like Pastel et al (2022), we found the angle of the final turn had no effect on end point accuracy in a healthy young adult population. In comparison, Adamo et al (2012), Anson et al (2019), andCuturi et al (2021) who investigated wayfinding in children and older adults, found that the turning angle did influence accuracy, with a larger angle of turn leading to reduced end point accuracy.…”
Section: Test-retest Reliability Of the Triangle Completion Testsupporting
confidence: 47%
See 3 more Smart Citations
“…Like Pastel et al (2022), we found the angle of the final turn had no effect on end point accuracy in a healthy young adult population. In comparison, Adamo et al (2012), Anson et al (2019), andCuturi et al (2021) who investigated wayfinding in children and older adults, found that the turning angle did influence accuracy, with a larger angle of turn leading to reduced end point accuracy.…”
Section: Test-retest Reliability Of the Triangle Completion Testsupporting
confidence: 47%
“…Virtual reality (VR) has been proposed as a means of controlling visual cues during spatial navigation tests without eliminating them entirely (Adamo et al, 2012;Cogné et al, 2017;Dorado et al, 2019a,b;Commins et al, 2020;Biju et al, 2021;Pastel et al, 2022). Early virtual environments used conventional computer screens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a large portion of these side effects can be managed by taking appropriate precautions, such as excluding patients prone to motion sickness and following post-immersion procedures [72]. Second, there are studies investigating the spatial perception of distance [73,74] and orientation [75] in VR environments. These studies have found that subjects perceive distances differently in VR than in real life, while the perception of orientation remains the same in VR.…”
Section: Vr For Rehabilitationmentioning
confidence: 99%